The Impact of Macroeconomic Factors on Non-performing Loans in the Western Balkans - Adelina Gashi; Saranda Tafa; Roberta Bajrami (Emerging Science Journal, 2022)
This paper analyzes the relationship of macroeconomic factors to the level of non-performing loans (NPLs) using the econometric models GMM, the Fixed Effect model, and the Random Effect model. This study aims to identify macroeconomic factors at the level of non-performing loans in the Western Balkans, measure their impact on non-performing loans, and thus fill the gap that exists between macroeconomic factors (consisting of economic growth) and those with more impact on NPLs. The methodology used to carry out this research was desk research. We used World Bank data from 2000–2019, processed with STATA software. Results show that macroeconomic factors have an impact on non-performing loans. It also proves that even when interacting with other variables, the level of bad debt has not been completely eliminated, despite economic growth in many countries. Third, throughout the study period, fixed effects estimates show that variables are not significant in a static context. According to the findings, the annual rates of GDP growth, final government consumption, the real interest rate, gross domestic savings, and the unemployment rate all have a favorable impact on NPLs. This research contributes to a deeper understanding of the relationship between macroeconomic factors and non-performing loans in the Western Balkans. Based on this, to help reduce loan risk and bad debt by the proper criteria, we propose a series of policy implications. These implications aim to improve the efficiency of banks in particular and the banking system as a whole. Doi: 10.28991/ESJ-2022-06-05-08 Full Text: PDF